Circulating CD34+VEGFR-2+ endothelial progenitor cells correlate with revascularization-mediated long-term improvement of cardiac function in patients with coronary chronic total occlusions. (1st January 2021) - Dai, Yuxiang; Huang, Jia; Chen, Yinyin; Chang, Shufu; Li, Chenguang; Lu, Hao; Ren, Daoyuan; Zhang, Feng; Huang, Zheyong; Qian, Juying; Ge, Lei; Ge, Junbo
Abstract: Background: Endothelial progenitor cells (EPCs) participate in angiogenesis and neocollateralization. This study assessed if circulating EPCs can predict long-term improvement of global left ventricular systolic function in patients with coronary chronic total occlusions (CTOs) underwent successful percutaneous coronary intervention (PCI). Methods: In this single-center, prospective, observational study, 115 consecutive patients with CTOs were evaluated by standard transthoracic echocardiography (ECHO) before and 9–12 months after PCI. Numbers of circulating putative EPCs were determined by flow cytometry analysis of mononuclear cells isolated from peripheral blood samples drawn before and 72 h after PCI. Results: At mean 11.3 ± 2.5 months post vs. before PCI (all P  < .05): by SAQ-7 summary scores, angina frequency, physical limitation and quality of life scores were greater; by ECHO, LVEDd decreased and LVEF increased, which were more significant in patients with Rentrop grades 2/3 vs. 0/1. At 72 h post vs. before PCI, CD34 + VEGFR-2 + CD133 − (0.82 ± 0.32 × 10 6 /L vs. 1.00 ± 0.39 × 10 6 /L, P  = .003), CD34 + VEGFR-2 + CD133 + (0.24 ± 0.12 × 10 6 /L vs. 0.27 ± 0.14 × 10 6 /L, P  = .028), and CD14 + Tie2 + VEGFR-2 + (6.60 ± 3.32 × 10 6 /L vs. 7.82 ± 3.91 × 10 6 /L, P  = .006) cell numbers were lower. The baseline levels of CD34 + VEGFR-2 + cells ( P  = .001) and CD14 + Tie2 + VEGFR-2 + cells ( P  < .001) were association with the grade of collateralization. In addition, the baseline and peri-procedural decrease of circulating CD34 + VEGFR-2 + cells correlated with the increase of LVEF ( P  < .001, P  < .001, respectively) and the decrease of LVEDd ( P  = .022, P  = .029, respectively) at follow-up. Conclusions: In this small study, the baseline levels of circulating CD34 + VEGFR-2+ EPCs and its reduction after successful revascularization of CTOs correlated with long-term improvement in global LV systolic function. Highlights: Revascularization of CTOs ameliorated clinical symptoms and LV function. Baseline CD34 + VEGFR-2 + cEPCs amount was associated with the improved LV function. PCI-mediated decrease of CD34 + VEGFR-2 + cEPCs related to the improved LV function.